Test for the improvement and evaluation of change of direction in team sports: a systematic review - Martin-Moya, R.; Gonzalez-Fernandez, F. T. (Journal of Physical Education and Sport, 2022)
Changes of direction (COD) are present in every type of sport there is, mainly in team sports where COD performance is particularly important because during game situations athletes frequently change speed and direction of movement as a way to avoid contact with opposing players in order to gain positional advantages that can lead to a goal or score for their team. This systematic review aimed to investigate how different types of training: strength, plyometrics, sprint, specific change of direction (COD) training or a combination of these approaches can improve CD performance. It also sought to determine what protocols or considerations should be taken into account for the improvement and assessment of COD through the different existing tests. This review included a total of 31 articles and was carried out following the recommendations of the current pre-established reporting elements for systematic reviews and meta-analyses. The following databases were consulted: ISI Web of Science (WOS), Scopus and Google Scholar. The results were presented based on two predominant themes: 1) Strength, plyometric and COD-specific training programs and 2) COD tests used for performance assessment in team sports. The most important finding of this review is that plyometric training, strength training, speed training, and specific COD training, the 505 and Illinois Test being the most used. A combination of these forms of training can be used to improve COD performance. The most important finding of this review was that plyometric training, strength training, speed training, specific training of the COD and a combination of these forms of training can all be used to develop the performance of the COD.